Achieving high performance in graphite nano-flakes reinforced titanium matrix composites through a novel reaction interface design. (30th April 2021) - Mu, X.N.; Zhang, H.M.; Chen, P.W.; Cheng, X.W.; Liu, L.; Ge, Y.X.; Xiong, N.; Zheng, Y.C.
Abstract: The present research was motivated by two unsettled questions. First, what are the detailed characteristics of the nanostructured interface in a nano-carbon/metal composite containing interfacial reaction products? Second, what other factors in interfacial carbide (not only its content) can influence the interface strength and mechanical properties, and if it is true? We developed a novel strategy to uncover these issues in graphite nano-flakes (GNFs)/Ti composites. Four GNFs/Ti samples with similar concentration of interfacial carbides were prepared under the guidance of DICTRA simulation. High-resolution transmission electron microscopy and precession assisted electron diffraction were applied to gain fundamental insight into the mechanisms that affect the characteristics of GNFs/Ti interfaces. The tensile results showed that the interfacial morphologies, GNFs-TiCx bonding strength, preferred orientation and growth defects were significant factors that were closely associated with the mesoscopic mechanical behavior. Interestingly, the heat-treated (HT) 1123K-600s GNFs/Ti composite exhibited the optimal tensile properties and superior GNFs-TiCx "synergetic" effect. The origin of such findings were explored from the viewpoint of nano-cracks/dislocation-interface interaction. This work provides a new insight in understanding the interfacial characteristics of GNFs/Ti composite, and underscores the importance of reaction interface design in strengthening of bulk GNFs/metal composite. Graphical abstract: Image 1